A calcium carbonate modified composite calcium sulfonate-based grease and preparation method thereof
By adding calcium carbonate particles of different particle sizes to the composite calcium sulfonate-based lubricating grease and pretreated micron-scale calcium carbonate to form a hydrophobic composite layer, the problem of insufficient lubrication of composite calcium sulfonate-based lubricating grease under low speed and high load conditions is solved. , significantly improves the anti-wear and friction reduction and water resistance of the grease.
Patent Information
- Application Number
- CN202310586215.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2023-03-29
- Filing Date
- 2023-05-23
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2043-05-23
AI Technical Summary
The existing composite calcium sulfonate-based grease cannot meet the lubrication needs of the equipment under extreme operating conditions with low rotation speed and extremely high loads, and needs to be modified to improve wear resistance and friction reduction.
Add nano- and micro-scale calcium carbonate particles to the composite calcium sulfonate-based lubricating grease to form an oil film boundary layer with better stiffness through gradient lubrication, and combine micro-scale calcium carbonate pretreated with graphite powder, nickel powder, lanthanum oxide and other pretreated Form a dense hydrophobic composite layer to improve the water resistance and corrosion resistance of the grease.
It significantly improves the anti-wear and friction resistance, high temperature resistance and mechanical stability of the grease, reduces bearing surface wear, and enhances the bearing capacity and corrosion resistance of the oil film.
Smart Images

Figure BDA0004243434120000101 
Figure BDA0004243434120000111 
Figure BDA0004243434120000121
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of lubricating greases, and more specifically, to a calcium carbonate-modified composite calcium sulfonate-based lubricating grease and a preparation method thereof. Background Art
[0002] Composite calcium sulfonate-based grease has attracted widespread attention as a new type of high-efficiency grease. Its thickening mechanism is that Newtonian high-base calcium sulfonate is transformed into non-Newtonian calcium sulfonate with thixotropy through a specific process, and is compounded with complex acids such as fatty acids and inorganic acids to obtain composite calcium sulfonate-based grease with excellent performance.
[0003] In modern industrial equipment used in mining, metallurgy, cement, and thermal power, bearings are increasingly being developed to handle heavy loads, large dimensions, and extended operating times, placing higher demands on lubricating materials within the bearings. While calcium sulfonate-based composite greases possess a certain extreme pressure load-carrying capacity, current production processes are unable to meet the extreme demands of low speeds and extremely high loads. Modification of calcium sulfonate-based composite greases requires specialized materials or processes. Summary of the Invention
[0004] In order to further improve the anti-wear and friction-reducing properties of composite calcium sulfonate-based grease, the present application provides a calcium carbonate-modified composite calcium sulfonate-based grease and a preparation method thereof.
[0005] In the first aspect, the present application provides a calcium carbonate modified composite calcium sulfonate-based grease, which adopts the following technical solution:
[0006] A calcium carbonate-modified composite calcium sulfonate-based grease comprising the following components in percentage by weight:
[0007] Complex calcium sulfonate based grease 80-99%;
[0008] Nano-scale calcium carbonate 1-10%;
[0009] Micronized calcium carbonate 1-10%, at least one of micronized calcium carbonate and nanometer calcium carbonate is added.
[0010] By adopting the above technical solution, calcium carbonate is a non-oil-soluble powdered solid inorganic filler, which is often used to enhance the lubricity and extreme pressure wear resistance of grease at high temperatures, reduce the friction coefficient and enhance the sealing performance, so that the grease product has a better lubrication effect in heavy-load equipment. Nano-scale calcium carbonate and / or micron-scale calcium carbonate are added to the composite calcium sulfonate-based grease, and the two are added in an appropriate proportion. The calcite crystal-type calcium carbonate structure forms boundary lubrication in the oil film, bearing impact loads or vibration loads or high loads, and can maintain good oil film load-bearing capacity at low speeds, which can improve the thermal stability and extreme pressure wear resistance of the composite calcium sulfonate-based grease.
[0011] Optionally, the following components are included in weight percentage:
[0012] Complex calcium sulfonate based grease 90-99%;
[0013] Nano-scale calcium carbonate 1-5%;
[0014] 1-5% micron calcium carbonate, at least one of micron calcium carbonate and nano calcium carbonate is added.
[0015] By adopting the above technical solution, the dosage of composite calcium sulfonate-based grease and micron-sized calcium carbonate and nano-sized calcium carbonate is more precise, and the resulting grease has better extreme pressure wear resistance, high temperature resistance and mechanical stability.
[0016] Optionally, the following components are included in weight percentage:
[0017] Complex calcium sulfonate grease 90-98%;
[0018] Nano-scale calcium carbonate 1-5%;
[0019] Micronized calcium carbonate 1-5%.
[0020] Optionally, the following components are included in weight percentage:
[0021] Complex calcium sulfonate grease 95-98%;
[0022] Nano-scale calcium carbonate 1-2.5%;
[0023] Micronized calcium carbonate 1-2.5%.
[0024] Optionally, the following components are included in weight percentage:
[0025] Complex calcium sulfonate based grease 90-95%;
[0026] Nano-scale calcium carbonate 2.5-5%;
[0027] Micronized calcium carbonate 2.5-5%.
[0028] Optionally, the following components are included in weight percentage:
[0029] Complex calcium sulfonate based grease 95-99%;
[0030] Nano-scale calcium carbonate 1-5%.
[0031] Optionally, the following components are included in weight percentage:
[0032] Complex calcium sulfonate based grease 95-99%;
[0033] Micronized calcium carbonate 1-5%.
[0034] Optionally, the particle size of the nano-scale calcium carbonate is 30-80 nm, and the particle size of the micron-scale calcium carbonate is 1-10 μm.
[0035] By adopting the above technical solution, micron-sized calcium carbonate and nano-sized calcium carbonate can cooperate with each other to improve the strength of the oil film and enhance the load-bearing capacity of the oil film.
[0036] Optionally, the composite calcium sulfonate-based grease comprises the following raw materials in parts by weight: 14-15 parts of base oil, 21-22 parts of overbased calcium sulfonate, 0.4-0.5 parts of n-butanol, 0.4-0.5 parts of glacial acetic acid, 1.5-1.6 parts of water, 1.4-1.5 parts of dodecyl stearic acid, 1-1.2 parts of calcium hydroxide and 0.8-1 parts of boric acid.
[0037] By adopting the above technical solution, a part of the dodecyl stearic acid can couple with the surface of nano-scale calcium carbonate and micro-scale calcium carbonate, and the rest of the dodecyl stearic acid has a certain amount of H + , showing acidity, so it will also react with high-base calcium sulfonate to increase the conversion rate. The reaction product, calcium dodecyl stearate, can increase the colloid stability of composite calcium sulfonate grease, increase the system's thickening ability, and improve the heat resistance and water resistance of the grease.
[0038] Optionally, the total base number of the overbased calcium sulfonate is 360-430 KOHmg / g.
[0039] Optionally, the base oil is selected from any one or more of mineral oil, polyalphaolefin oil, and ester oil.
[0040] In a second aspect, the present application provides a method for preparing a calcium carbonate-modified composite calcium sulfonate-based grease, which adopts the following technical solution:
[0041] A method for preparing a calcium carbonate-modified composite calcium sulfonate-based grease comprises the following steps:
[0042] (1) Add overbased calcium sulfonate, 45-47% base oil and water to a reactor, heat to 50-60°C, and homogenize for 30-60 minutes;
[0043] (2) Add n-butanol and glacial acetic acid, raise the temperature to 70-80°C, and react for 60-90 minutes;
[0044] (3) adding calcium hydroxide, boric acid and dodecyl stearic acid, raising the temperature to 90-99° C., and reacting for 60-90 minutes;
[0045] (4) heating to 100-110°C for dehydration and dealcoholization, and keeping the temperature for 90-120 minutes;
[0046] (5) Continue heating to 170-180°C, keep warm for 5-10 minutes, then cool to 120°C, add the remaining base oil, mix well, and obtain a composite calcium sulfonate-based grease;
[0047] (6) When the temperature is lowered to 80-90° C., nano-scale calcium carbonate and / or micro-scale calcium carbonate are added, mixed, homogenized, and degassed to obtain a calcium carbonate-modified composite calcium sulfonate-based grease.
[0048] By adopting the above technical solution, two types of calcium carbonate particles with different particle sizes are added in the later stage of the preparation process of the composite calcium sulfonate-based grease. Through the gradient lubrication effect of calcium carbonate with two different particle sizes, nanometer and micrometer, an oil film boundary layer with better rigidity can be formed on the surface of the friction pair under low speed and heavy load, so as to keep the oil film continuous and not broken, effectively reduce the wear on the bearing surface, and improve the anti-wear and friction reduction performance and high temperature performance of the composite calcium sulfonate-based grease. The preparation method is simple and can effectively reduce energy consumption and production difficulty.
[0049] Optionally, n-butanol and glacial acetic acid are added in the form of aqueous solution with a mass concentration of 30-40%, and boric acid is added in the form of a hot aqueous solution of boric acid at a temperature of 80-90° C. with a mass concentration of 30-40%.
[0050] Optionally, the micron-sized calcium carbonate is pretreated as follows:
[0051] Graphite powder, lanthanum oxide and nickel powder are added to water, sodium lauryl sulfate is added, and ultrasonic treatment is performed to make a mixed solution. The mass ratio of graphite powder, lanthanum oxide and nickel powder is 1:0.1-0.3:2-3;
[0052] Adding an ethanol solution of tetradecanoic acid to a titanium dioxide sol and stirring uniformly to prepare a composite sol, wherein the mass ratio of the titanium dioxide sol to the ethanol solution of tetradecanoic acid is 0.1-0.2:2;
[0053] Add micron-sized calcium carbonate to the mixed solution, heat in a water bath at 70-75°C and stir for 45-60 minutes, filter and dry to obtain an intermediate;
[0054] The intermediate is added to the composite sol, filtered and dried after 1-3 minutes.
[0055] The oil film formed by composite calcium sulfonate-based grease is easily destroyed by water, and the presence of water can easily lead to bearing corrosion. By adopting the above technical solution, the micron-sized calcium carbonate is pretreated to improve the hydrophobicity of the micron-sized calcium carbonate, thereby enhancing the water resistance and corrosion resistance of the grease. The graphite powder is first wetted and dispersed with sodium lauryl sulfate to ensure uniform dispersion of the graphite powder. After the graphite powder, nickel powder and lanthanum oxide are mixed to form a solution, it is mixed with micron-sized calcium carbonate to form a composite layer of graphite-nickel powder and lanthanum oxide on the micron-sized calcium carbonate. The graphite powder mainly exists in two forms: embedded and adsorbed. The La in lanthanum oxide 3+ The larger particle size can promote the diffusion of graphite particles and significantly reduce the agglomeration of graphite in the composite layer. In addition, rare earth elements have strong adsorption capacity, which can make the surface of graphite particles adsorb more positive charges, improve its deposition ability on the surface of micron-sized calcium carbonate, make the composite layer uniform and dense, smooth and flat, reduce the roughness of the composite layer, and the graphite particles are uniform in size and embedded in the nickel and lanthanum oxide composite, which increases the wear resistance and the hardness of the composite layer, thereby improving the rigidity of the oil film. Then, the micron-sized calcium carbonate with the composite layer is treated with titanium dioxide sol containing tetradecanoic acid. During drying and solidification, the solvent in the sol evaporates and the The hydroxyl groups react with the hydroxyl groups contained in the graphite on the composite layer to produce a condensation reaction, and the generated water and organic groups are evaporated. During the drying process, the volume of the gel film gradually shrinks while the adhesion to the composite layer gradually increases. A strong chemical bond is formed between the sol and the composite layer. Finally, a stable network titanium dioxide film is formed on the composite layer of the intermediate, which closes the gaps on the surface of the composite layer, improves the density of the composite layer, increases water resistance, can effectively isolate the corrosive medium from contact with the bearing, and prevents the free diffusion and migration of oxygen and electrons at the solution and metal interface. The corrosion dynamics are effectively suppressed, the corrosion process is slowed down, and the titanium dioxide film itself has high corrosion resistance. The hydroxyl group at one end of the tetradecanoic acid will undergo a condensation reaction with the hydroxyl group on the composite layer. Its skeleton is also a CC main chain, and the methyl group at one end also has a low surface energy. Its special molecular structure and atomic arrangement cause its surface energy to decrease rapidly, and it has special properties such as stable chemical properties, good compatibility, waterproofness, and anti-fouling. In addition, the tetradecanoic acid and titanium dioxide are cross-linked and coupled with hydrolysis, and self-assemble on the surface of the composite layer to form a microstructure combining nanometers and micrometers. At the same time, the polymerization of the hydrophobic CC main chain and titanium dioxide greatly increases the surface contact angle, further improves the hydrophobicity, enhances water resistance, makes the oil film less likely to be destroyed by water, and prevents the presence of water, which causes corrosion of metal bearings.
[0056] Optionally, the mass ratio of the micron-sized calcium carbonate to the mixed solution is 1:0.6-0.9, and the mass ratio of the intermediate to the composite sol is 1:0.7-0.8.
[0057] By adopting the above technical solution and pretreating the micron-sized calcium carbonate with the above dosage ratio, a dense and uniform hydrophobic composite layer can be formed on the micron-sized calcium carbonate, thereby improving the water resistance and water resistance of the oil film and enhancing the corrosion resistance of the grease.
[0058] In summary, this application has the following beneficial effects:
[0059] 1. Because this application utilizes composite calcium sulfonate in combination with calcium carbonate particles of varying particle sizes, and because composite calcium sulfonate-based greases exhibit excellent performance, they are often used in demanding environments, such as low-speed, heavily loaded equipment bearings. By adding calcium carbonate particles of varying particle sizes late in the preparation process of the composite calcium sulfonate-based grease, the gradient lubrication effect of the nano- and micron-sized calcium carbonates can form a stiffer oil film boundary layer on the surface of the friction pair at low speeds and heavy loads, maintaining a continuous, unbroken oil film. This effectively reduces bearing surface wear and enhances the anti-wear and friction-reducing properties and high-temperature performance of the composite calcium sulfonate-based grease.
[0060] 2. In this application, graphite powder, nickel powder, lanthanum oxide, etc. are preferably used to pretreat the micron-sized calcium carbonate to form a lubricating and wear-resistant composite layer on the micron-sized calcium carbonate, and titanium dioxide sol containing tetradecanoic acid is used to seal the gaps in the micron-sized calcium carbonate containing the composite layer, thereby further improving the density of the micron-sized calcium carbonate surface and the hydrophobicity of the micron-sized calcium carbonate, thereby enhancing the water resistance and corrosion resistance of the grease film. DETAILED DESCRIPTION
[0061] Example
[0062] Example 1: A calcium carbonate-modified composite calcium sulfonate-based grease, comprising 95% composite calcium sulfonate-based grease, 2.5% nano-scale calcium carbonate and 2.5% micron-scale calcium carbonate (% is weight percentage), the particle size of the nano-scale calcium carbonate is 80nm, the particle size of the micron-scale calcium carbonate is 10μm, and the composite calcium sulfonate-based grease comprises the following raw materials by weight: 1500g high-base calcium sulfonate, 2200g base oil, 150g water, 50g n-butanol, 50g glacial acetic acid, 100g calcium hydroxide, 80g boric acid and 140g dodecyl stearic acid, the total base number of the high-base calcium sulfonate is 400KOHmg / g, the base oil is 150BS, and the viscosity at 40°C is 430mm 2 / s.
[0063] The preparation method of the calcium carbonate modified composite calcium sulfonate-based grease comprises the following steps:
[0064] (1) Add 1500 g of overbased calcium sulfonate, 1000 g of base oil and 150 g of water to a reactor, heat to 50°C and homogenize for 60 min;
[0065] (2) Add 50 g of n-butanol and 50 g of glacial acetic acid, raise the temperature to 80°C, and react for 60 min;
[0066] (3) Add 100 g of calcium hydroxide, 80 g of boric acid, and 140 g of dodecyl stearic acid, raise the temperature to 95° C., and react for 60 min;
[0067] (4) heating to 110°C for dehydration and dealcoholization, and keeping the temperature for 120 min;
[0068] (5) Continue heating to 175°C, keep warm for 10 minutes, then cool to 120°C, add 1200g of base oil, mix well, and obtain composite calcium sulfonate-based grease;
[0069] (6) When the temperature is lowered to 80° C., 200 g of nano-scale calcium carbonate and 200 g of micro-scale calcium carbonate are added, mixed, homogenized, and degassed to obtain a calcium carbonate-modified composite calcium sulfonate-based grease.
[0070] Example 2: A calcium carbonate-modified composite calcium sulfonate-based grease, comprising 95% composite calcium sulfonate-based grease and 5% nano-scale calcium carbonate (% is weight percentage), the composite calcium sulfonate-based grease comprising the following raw materials by weight: 1400g high-base calcium sulfonate, 2100g base oil, 160g water, 40g 40% n-butanol aqueous solution by mass concentration, 40g 40% glacial acetic acid aqueous solution by mass concentration, 120g calcium hydroxide, 100g 40% hot boric acid aqueous solution at a temperature of 80°C and a mass concentration of 40%, and 150g dodecyl stearic acid. The total base number of the high-base calcium sulfonate is 430KOHmg / g, the base oil is 150BS, and the viscosity at 40°C is 430mm. 2 / s.
[0071] The preparation method of the calcium carbonate modified composite calcium sulfonate-based grease comprises the following steps:
[0072] (1) Add 1400 g of overbased calcium sulfonate, 1000 g of base oil and 160 g of water to a reactor, heat to 60°C and homogenize for 30 min;
[0073] (2) Add 40 g of n-butanol and 40 g of glacial acetic acid, raise the temperature to 70°C, and react for 90 min;
[0074] (3) Add 120 g of calcium hydroxide, 100 g of boric acid, and 150 g of dodecyl stearic acid, raise the temperature to 90° C., and react for 90 min;
[0075] (4) heating to 100°C for dehydration and dealcoholization, and keeping the temperature for 90 minutes;
[0076] (5) Continue heating to 180°C, keep warm for 5 minutes, then cool to 120°C, add 1100g of base oil, mix well, and obtain composite calcium sulfonate-based grease;
[0077] (6) When the temperature drops to 90° C., 200 g of nano-scale calcium carbonate and 200 g of micro-scale calcium carbonate are added, mixed, homogenized, and degassed to obtain a calcium carbonate-modified composite calcium sulfonate-based grease.
[0078] Example 3: A calcium carbonate-modified composite calcium sulfonate-based grease, which differs from Example 2 in that it comprises 95% composite calcium sulfonate-based grease and 5% micron-sized calcium carbonate (% is weight percentage).
[0079] Example 4: A calcium carbonate-modified composite calcium sulfonate-based grease, which differs from Example 2 in that it comprises 90% composite calcium sulfonate-based grease, 5% nano-scale calcium carbonate and 5% micron-scale calcium carbonate (% is weight percentage), the particle size of the nano-scale calcium carbonate is 30nm, and the particle size of the micron-scale calcium carbonate is 1μm.
[0080] Example 5: A calcium carbonate-modified composite calcium sulfonate-based grease, which differs from Example 1 in that it comprises 98% composite calcium sulfonate-based grease, 1% nano-scale calcium carbonate and 1% micron-scale calcium carbonate (% is weight percentage), the particle size of the nano-scale calcium carbonate is 30nm, and the particle size of the micron-scale calcium carbonate is 1μm.
[0081] The preparation method of the calcium carbonate modified composite calcium sulfonate-based grease comprises the following steps:
[0082] (1) Add 1500 g of overbased calcium sulfonate, 1000 g of base oil and 150 g of water to a reactor, heat to 50°C and homogenize for 60 min;
[0083] (2) Add 50 g of n-butanol and 50 g of glacial acetic acid, raise the temperature to 80°C, and react for 60 min;
[0084] (3) Add 100 g of calcium hydroxide, 80 g of boric acid, and 140 g of dodecyl stearic acid, raise the temperature to 95° C., and react for 60 min;
[0085] (4) heating to 110°C for dehydration and dealcoholization, and keeping the temperature for 120 min;
[0086] (5) Continue heating to 175°C, keep warm for 10 minutes, then cool to 120°C, add 1200g of base oil, mix well, and obtain composite calcium sulfonate-based grease;
[0087] (6) When the temperature is lowered to 80° C., 40 g of nano-scale calcium carbonate and 40 g of micro-scale calcium carbonate are added, mixed, homogenized, and degassed to obtain a calcium carbonate-modified composite calcium sulfonate-based grease.
[0088] Example 6: A calcium carbonate-modified composite calcium sulfonate-based grease, which differs from Example 1 in that no nano-scale calcium carbonate and micro-scale calcium carbonate are added.
[0089] Example 7: A calcium carbonate-modified composite calcium sulfonate-based grease. The difference from Example 1 is that the micron-sized calcium carbonate is pretreated as follows:
[0090] (1) adding graphite powder, lanthanum oxide, and nickel powder to water, adding sodium lauryl sulfate, and ultrasonically homogenizing to prepare a mixed solution, wherein the mass ratio of graphite powder, lanthanum oxide, and nickel powder is 1:0.1:2, and the mass ratio of graphite powder, water, and sodium lauryl sulfate is 1:5:0.05;
[0091] (2) adding an ethanol solution of tetradecanoic acid to the titanium dioxide sol and stirring uniformly to prepare a composite sol, wherein the mass ratio of the titanium dioxide sol to the ethanol solution of tetradecanoic acid is 0.1:2;
[0092] (3) adding micron-sized calcium carbonate to the mixed solution, heating in a water bath at 70° C. and stirring for 60 min, filtering, and drying to obtain an intermediate, wherein the mass ratio of micron-sized calcium carbonate to the mixed solution is 1:0.6;
[0093] (4) The intermediate was added to the composite sol, filtered and dried after 3 minutes, and the mass ratio of the intermediate to the composite sol was 1:0.7.
[0094] Example 8: A calcium carbonate-modified composite calcium sulfonate-based grease, which differs from Example 1 in that the micron-sized calcium carbonate undergoes the following pretreatment:
[0095] (1) adding graphite powder, lanthanum oxide, and nickel powder to water, adding sodium lauryl sulfate, and ultrasonically homogenizing to prepare a mixed solution, wherein the mass ratio of graphite powder, lanthanum oxide, and nickel powder is 1:0.3:3, and the mass ratio of graphite powder, water, and sodium lauryl sulfate is 1:5:0.05;
[0096] (2) adding an ethanol solution of tetradecanoic acid to the titanium dioxide sol and stirring uniformly to prepare a composite sol, wherein the mass ratio of the titanium dioxide sol to the ethanol solution of tetradecanoic acid is 0.2:2;
[0097] (3) adding micron-sized calcium carbonate to the mixed solution, heating in a water bath at 75° C. and stirring for 45 min, filtering, and drying to obtain an intermediate, wherein the mass ratio of micron-sized calcium carbonate to the mixed solution is 1:0.9;
[0098] (4) The intermediate was added to the composite sol, filtered and dried after 1 minute, and the mass ratio of the intermediate to the composite sol was 1:0.8.
[0099] Example 9: A calcium carbonate-modified composite calcium sulfonate-based grease, which differs from Example 8 in that lanthanum oxide is not added to the mixed solution.
[0100] Example 10: A calcium carbonate-modified composite calcium sulfonate-based grease, which differs from Example 8 in that no graphite powder is added to the mixed solution.
[0101] Example 11: A calcium carbonate-modified composite calcium sulfonate-based grease, which differs from Example 8 in that no nickel powder is added to the mixed solution.
[0102] Example 12: A calcium carbonate-modified composite calcium sulfonate-based grease. The difference from Example 8 is that the micron-sized calcium carbonate is pretreated as follows:
[0103] (1) adding graphite powder, lanthanum oxide, and nickel powder to water, adding sodium lauryl sulfate, and ultrasonically homogenizing to prepare a mixed solution, wherein the mass ratio of graphite powder, lanthanum oxide, and nickel powder is 1:0.3:3, and the mass ratio of graphite powder, water, and sodium lauryl sulfate is 1:5:0.05;
[0104] (3) Add micron-sized calcium carbonate to the mixed solution, heat in a water bath at 75° C. and stir for 45 minutes, filter, and dry. The mass ratio of micron-sized calcium carbonate to the mixed solution is 1:0.9.
[0105] Example 13: A calcium carbonate-modified composite calcium sulfonate-based grease, which differs from Example 8 in that no ethanol solution of tetradecanoic acid is added to the composite sol.
[0106] Comparative Example
[0107] Comparative Example 1: A calcium carbonate-modified composite calcium sulfonate-based grease, which differs from Example 1 in that the preparation method is:
[0108] (1) Add 1500 g of overbased calcium sulfonate, 1000 g of base oil and 150 g of water to a reactor, heat to 50°C and homogenize for 60 min;
[0109] (2) Add 50 g of n-butanol and 50 g of glacial acetic acid, raise the temperature to 80°C, and react for 60 min;
[0110] (3) Add 100 g of calcium hydroxide, 80 g of boric acid, 140 g of dodecyl stearic acid, 200 g of nano-scale calcium carbonate, and 200 g of micro-scale calcium carbonate, raise the temperature to 95° C., and react for 60 min;
[0111] (4) heating to 110°C for dehydration and dealcoholization, and keeping the temperature for 120 min;
[0112] (5) Continue to heat up to 175°C, keep warm for 10 minutes, then cool down to 120°C, add 1200g of base oil, mix well, and prepare calcium carbonate modified composite calcium sulfonate-based grease.
[0113] Comparative Example 2: A method for preparing a composite calcium sulfonate grease containing nano-calcium carbonate, comprising the following steps: adding 200 kg HVI500 (40 ° C kinematic viscosity: 97 mm 2 / s, accounting for 37.8% of the total weight of the base oil) and 400kg of synthetic calcium sulfonate with a total base number of 250mgKOH / g (40% of the total amount of the grease raw materials), stirred and heated to 60℃, 50kg of water and 50kg of HBS (5% of the total amount of the grease raw materials) were added, stirred and heated to 80℃ for constant temperature conversion reaction until the conversion was complete (monitored by infrared spectroscopy at 862cm for amorphous calcium carbonate). -1 The characteristic absorption peak at (1) disappears, and the reaction lasts for about 0.5 to 1 hour. 10 kg of nano-calcium carbonate (1% of the total amount of the grease raw material) is added and stirred for 5 minutes. Then, a hot solution of 5 kg of boric acid (0.5% of the total amount of the grease raw material) and 25 kg of water and 5 kg of 12-hydroxystearic acid (0.5% of the total amount of the grease raw material) are added in sequence. After stirring and dehydration, 200 kg of HVI500 (37.8% of the total weight of the base oil) is added. The dehydration is continued and the temperature is raised to 180° C. After maintaining the temperature for 10 minutes, heating is stopped. 1 kg of diisooctyldiphenylamine (0.1% of the total amount of the grease raw material) and 129 kg of HVI500 are added. The mixture is stirred and cooled to below 100° C. and homogenized and degassed in a homogenizer to obtain the finished product. The base oil added in this embodiment is 52.9% of the total amount of the grease raw material.
[0114] Comparative Example 3: A method for preparing a calcium carbonate whisker modified composite calcium sulfonate grease, comprising the following steps: adding 40 g of 150BS (Rwe Group, the same below) and 1.5 g of isopropyl dioleyl (dioctyl phosphate) titanate KH-101 (Nanjing Nengde Chemical Co., Ltd.) into a stirring container with a volume of 100 mL, heating and stirring to 80°C, then adding 150 g of calcium carbonate whisker NP-CW2 (Shanghai Fengzhu Composite New Material Technology Co., Ltd., the same below), and reacting at 85°C for 15 minutes; then adding 150 g of stearic acid, and continuing the reaction for 15 minutes.
[0115] To a 1L reactor, add 413.5g of 150BS and 300g of overbased calcium sulfonate T106D, heat and stir to 85°C, then add 50g of water and 30g of glacial acetic acid in sequence, maintain 95°C and continue stirring for 100 minutes, until the system gradually becomes viscous; add the modified whiskers in the above stirring container to the reactor, maintain 95°C and continue the reaction for 10 minutes; then raise the temperature to 140°C and continue stirring for 30 minutes to carry out a dehydration reaction; after dehydration, cool the grease to 110°C, grind and homogenize, and degas to obtain a calcium carbonate whisker-modified composite calcium sulfonate grease.
[0116] Performance testing
[0117] The greases produced in Examples 1-13 and Comparative Examples 1-3 were tested according to the following method. The test results are shown in Table 1.
[0118] 1. Working cone penetration: Test in accordance with GB / T269-1991 "Determination of cone penetration of grease and petroleum grease". The larger the working cone penetration value, the softer the grease, and vice versa.
[0119] 2. Dropping point: Test in accordance with GB / T3498-1983 "Determination of Dropping Point of Lubricating Grease over a Wide Temperature Range". The higher the dropping point, the better the heat resistance of the grease and the better its performance at high temperatures.
[0120] 3. Stencil oil separation: Tested in accordance with SH / T0324 "Determination of Grease Stencil Oil Separation (Static Method)" to reflect the colloid stability of grease under high temperature conditions. The smaller the oil separation, the better the stability, and the less likely it is to have thin oil during storage and use;
[0121] 4. Evaporation capacity: tested in accordance with GB / T7325-1987 "Determination of evaporation loss of grease and lubricating oil", indicating the degree of volatilization of grease when used under high temperature conditions. The smaller the evaporation capacity, the better;
[0122] 5. Copper sheet corrosion: Test according to method B of GB / T7326-1987 "Grease Copper Sheet Corrosion Test";
[0123] 6. Corrosion resistance: Tested in accordance with GB / T5018-2008 "Test method for corrosion resistance of lubricating grease";
[0124] 7. Four-ball testing machine: Test in accordance with SH / T0202-1992 "Determination of extreme pressure properties of grease (four-ball machine method)", where P B Indicates the maximum non-seizure load, which measures the ink strength of the grease. The larger the measured value, the better the lubrication performance of the grease. N Indicates the sintering load. The higher the sintering load, the better the extreme pressure lubricity of the grease.
[0125] 8. Wear scar diameter: Test according to SH / T0204-1992 "Determination of anti-wear properties of grease (four-ball machine method)". The smaller the wear scar diameter, the better the lubricity of the grease.
[0126] 9. Water loss: The test is carried out in accordance with SH / T0109 "Determination of water resistance of grease". The smaller the test value, the better the water resistance of the grease.
[0127] Table 1 Performance test of calcium carbonate modified composite calcium sulfonate-based grease prepared in Examples 1-6
[0128]
[0129] The data in Table 1 demonstrates that Examples 1-3 differ in the effects of varying ratios of micronized and nanometer-sized calcium carbonate on grease performance, even with the same total calcium carbonate addition. Analysis of the physical and chemical properties of the greases produced in these examples demonstrates that the greases of this invention exhibit excellent colloidal stability, superior lubricity, and extreme pressure and anti-wear properties. The tribological properties of Examples 1-3 are superior to those of Comparative Example 1, making them suitable for bearing lubrication in heavy-duty equipment. Example 1, in particular, exhibits both excellent extreme pressure and anti-wear properties and anti-friction and friction reduction, meeting lubrication requirements at both room and high temperatures.
[0130] The difference between Example 1 and Examples 4-5 is that when the ratio between micron-sized calcium carbonate and nano-sized calcium carbonate is the same, the wear resistance of the grease decreases with the increase in the amount of calcium carbonate added. In Examples 2 and 3, no micron-sized calcium carbonate and nano-sized calcium carbonate are added, respectively. Compared with Example 1, the wear resistance is reduced. The friction properties of the greases prepared in Examples 1 and Examples 4-5 are better than those in Example 6, indicating that the addition of multiple layers of calcium carbonate helps to improve the load-bearing capacity and oil film stiffness of the composite calcium sulfonate-based grease.
[0131] Performance test of calcium carbonate modified composite calcium sulfonate-based grease prepared in Examples 7-13
[0132]
[0133]
[0134] Compared with Example 1, in Examples 7-8, the wear resistance of the grease prepared by treating micron-sized calcium carbonate with graphite powder, nickel powder, etc. is improved, the water loss is reduced, and the water resistance is increased; in Examples 9-11, lanthanum oxide, graphite powder and nickel powder are not added to the mixed solution respectively. Compared with Example 8, the wear scar diameter of the grease prepared in Examples 9-11 is increased, the wear resistance is weakened, and the water resistance is slightly reduced. Compared with Example 8, in Example 12, the micron-sized calcium carbonate is not treated with a composite sol, and the water resistance of the grease is reduced. In Example 13, tetradecanoic acid is not added to prepare the composite sol, and the water resistance of the grease is weakened.
[0135] Performance test of calcium carbonate modified composite calcium sulfonate-based grease prepared in comparative examples 1-3
[0136]
[0137]
[0138] In Comparative Example 1, nano-scale calcium carbonate and micron-scale calcium carbonate were added during the preparation of the composite calcium sulfonate-based grease, rather than during the cooling process of the composite calcium sulfonate-based grease as in Example 1. The wear resistance and lubricating properties of the grease prepared in Comparative Example 1 were inferior to those of Example 1.
[0139] Comparative Examples 2 and 3 are greases containing nano-calcium carbonate and calcium carbonate whiskers. Compared with Comparative Examples 2-3, the grease prepared in Example 1 has higher extreme pressure wear resistance and lubricity.
[0140] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make non-creative modifications to the present embodiment as needed, but as long as they are within the scope of the claims of the present application, they are protected by the patent law.
Claims
1. A calcium carbonate modified composite calcium sulfonate based grease, characterized in that: The composition includes the following weight percentages: Calcium sulfonate complex grease 90-98%; Nano calcium carbonate 1-5%; Micronized calcium carbonate 1-5%; The composite calcium sulfonate-based grease comprises the following raw materials in parts by weight: 14-15 parts base oil, 21-22 parts overbased calcium sulfonate, 0.4-0.5 parts n-butanol, 0.4-0.5 parts glacial acetic acid, 1.5-1.6 parts water, 1.4-1.5 parts dodecyl hydroxystearic acid, 1-1.2 parts calcium hydroxide and 0.8-1 parts boric acid; The preparation method of the calcium carbonate modified composite calcium sulfonate-based grease comprises the following steps: (1) Add high base calcium sulfonate, 45-47% base oil and water to the reactor, heat to 50-60°C, and homogenize for 30-60 minutes; (2) Add n-butanol and glacial acetic acid, raise the temperature to 70-80°C, and react for 60-90 minutes; (3) Add calcium hydroxide, boric acid and dodecyl stearic acid, raise the temperature to 90-99°C, and react for 60-90 minutes; (4) Heating to 100-110°C for dehydration and dealcoholization, keeping the temperature for 90-120 minutes; (5) Continue to heat up to 170-180°C, keep warm for 5-10 minutes, then cool down to 120°C, add the remaining base oil, mix evenly, and obtain composite calcium sulfonate-based grease; (6) When the temperature drops to 80-90°C, add nano-scale calcium carbonate and micro-scale calcium carbonate, mix, homogenize, and degas to obtain a calcium carbonate-modified composite calcium sulfonate-based grease; The micron-sized calcium carbonate is pretreated as follows: Add graphite powder, lanthanum oxide and nickel powder into water, add sodium dodecyl sulfate, and ultrasonically homogenize to prepare a mixed solution, wherein the mass ratio of graphite powder, lanthanum oxide and nickel powder is 1:0.1-0.3:2-3; Adding the ethanol solution of tetradecanoic acid to the titanium dioxide sol and stirring evenly to obtain a composite sol, wherein the mass ratio of the titanium dioxide sol to the ethanol solution of tetradecanoic acid is 0.1-0.2:2; Add micron-sized calcium carbonate to the mixed solution, heat in a water bath at 70-75°C and stir for 45-60 minutes, filter and dry to obtain an intermediate; The intermediate is added to the composite sol, filtered and dried after 1-3 minutes.
2. The calcium carbonate modified composite calcium sulfonate based grease according to claim 1, characterized in that: The particle size of the nano-scale calcium carbonate is 30-80 nm, and the particle size of the micron-scale calcium carbonate is 1-10 μm.
3. The calcium carbonate modified composite calcium sulfonate based grease according to claim 1, characterized in that: The total base number of the overbased calcium sulfonate is 360-430 KOHmg / g.
4. The calcium carbonate modified composite calcium sulfonate based grease according to claim 1, characterized in that: The base oil is selected from any one or more of mineral oil, polyalphaolefin oil, and ester oil.
5. The calcium carbonate modified composite calcium sulfonate based grease according to claim 1, characterized in that: The mass ratio of the micron-sized calcium carbonate to the mixed solution is 1:0.6-0.9, and the mass ratio of the intermediate to the composite sol is 1:0.7-0.8.
